Nanotechnology-Based Diagnostics and Therapy for Pathogen-Related Infections in the CNS - Tamil Selvan, Subramanian; Padmanabhan, Parasuraman; Zoltán Gulyás, Balázs (ACS chemical neuroscience, 2020)
The central nervous system (CNS) encompasses the brain, spinal cord, and nerves, where both brain and spinal cord are safeguarded by the meninges. However, serious bacterial, viral, or fungal infection in the brain causes life-threatening diseases such as meningitis. Engineered nanostructures hold great promise for not only in the diagnosis but also for combating microbial drug resistance owing to their high surface area and innate antibacterial activity. We delineate several nanoparticle-based approaches to enhance the CNS delivery of drugs across the blood-brain barrier (BBB). While pathogens invade the CNS by phagocytosis or receptor (e.g., EphA2)-mediated transcytosis, most of the nanoparticles cross the BBB via receptor-mediated transcytosis (e.g., antibody, peptide, protein). We also provide our perspectives on the diagnostic pathways based on nanotechnology for the detection of pathogens in the brain, thereby opening up new therapeutic avenues.